Fenomena Thrifting Fashion di Era Milenial (Studi Kasus Mahasiswa Sekolah Tinggi Ilmu Ekonomi Jambatan Bulan Timika) - Sintiani, Sintiani; Fandi, Eka Wahyu; Dian, Elsa (ProBisnis : Jurnal Manajemen, 2024)
This study aims to analyze the influence of Price, Quality, Environment, and Motivation variables on the interest of STIE Jambatan Bulan students in participating in thrifting fashion practices. The method used is a quantitative approach with multiple linear regression analysis. Data were collected by distributing questionnaires to 50 respondents who were students involved in thrifting practices. The results showed that the Price and Motivation variables had a significant influence on student interest, where more affordable prices and high levels of motivation contributed positively to their decision to choose thrifting. On the other hand, the Quality and Environment variables did not show a significant influence on student interest. These findings provide important insights for thrifting business actors to focus more on competitive pricing strategies and motivational promotions to increase consumer interest. This study also contributes to the understanding of the factors that influence the interest of the younger generation in thrifting fashion practices.